VALIDITAS DAN KEPRAKTISAN DESAIN PEMBELAJARAN BERBASIS MASALAH TERKAIT DENGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS PESERTA DIDIK - Rainal .I. I; Priyanda .R; Mery D. C. H; Herlina .M (Universitas Samudra, 2020)
This article is the result of design-based research that aims to compile and explore mathematics learning designs with problem-based learning models. In this article, we will discuss the level of validity and practicality of learning designs equipped with Student Worksheets (LKPD). The learning design was compiled with a needs and content analysis then validated by a team of experts before being applied to a limited trial at one of the State Madrasah Aliyah in Bandung Regency, West Java. The level of validity is determined based on the results of the validation of 3 mathematics education lecturers and a teacher at the research location. The assessment given is 88% with very valid criteria. The value of the LKPD validation level gets the value of the expert team on very valid criteria with an average assessment of 86%. The level of practicality reviewed in the study is the aspect of assistance and convenience. At each learning step, students gave a positive response to practicality with an average response value of 3.87 from a maximum score of 5. As for the interpretation of the mean value, the students' responses were in good criteria.